Buddhism and the Don Kalmyk Cossacks in the Sociocultural Space of Russia - Ulanov, Mergen S.; Andreeva, Aria A. (The New Research of Tuva, 2021)
This article examines the features of the history of Buddhism among the Don Kalmyk Cossacks. Thus, it is noted that among the Cossacks there were traditionally and historically followers of different religions. The very situation of the formation of the Kalmyk Buddhists as the Cossacks is considered as atypical.Historical events in the region inhabited by the Kalmyks as subjects of the Russian Empire resulted in a situation when some of them moved to the banks of the Don in the 17th century, where they received the status of Cossack troops. Despite their geographical isolation from the bulk of the Kalmyk people and integration into the Don Cossack society, the Kalmyk Cossacks managed to preserve their ethnic and confessional identity. Moreover, Buddhism became the overriding factor in retaining the national identity of the Kalmyks. It was Buddhism that was distinguishing them from the other peoples of the Province of the Don Cossack Host, having become a symbol of their ethnic identity and consolidation.The Don Cossack administration was in turn interested in the Kalmyks as a significant military force, whereby religious differences were fading into the background. Despite attempts to limit the number of khuruls and the Kalmyk clergy, as well as to bring the Buddhist church of the Don Kalmyks under control, the latter was a considerably cohesiv
Keywords: Buddhism; Buddhist church; Buddhist clergy; Buddhism of Russia; khurul; Kalmyks; Kalmykia; Don Kalmyks; Kalmyk Cossacks; province of the Don Cossack Host; Don; Buddhist identity